2008
DOI: 10.1002/dvdy.21526
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid induces prostatic bud formation

Abstract: Formation of prostatic buds from the urogenital sinus (UGS) to initiate prostate development requires localized action of several morphogenetic factors. This report reveals all-trans-retinoic acid (RA) to be a powerful inducer of mouse prostatic budding that is associated with reciprocal changes in expression of two regulators of budding: sonic hedgehog (Shh) and bone morphogenetic protein 4 (Bmp4). Localization of retinoid signaling and expression of RA synthesis, metabolism, and receptor genes in the UGS on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 85 publications
(93 reference statements)
1
48
1
2
Order By: Relevance
“…Only the assembly of Cx32 into GJs appeared to be significantly facilitated by 9-CRA and ATRA as neither the assembly nor degradation of adherens junction associated proteins, E-cadherin and α and β catenin, were significantly affected although the assembly of tight junction associated protein, occludin, appeared to be enhanced. The significance of these findings is further underscored by the fact that both androgens and retinoids have been documented to maintain the polarized and differentiated state of epithelial cells of normal prostate and prostatic tumors [19], [42][45], and all have been shown to have pleiotypic effects by acting as transcription factors [1], [3], [5], [46]. Our findings also showed that Cx32 expression potentiated the growth inhibitory effect of androgens and retinoids in LNCaP-32 cells, which indicates that their growth inhibitory and chemopreventive effects in prostate might be related to their ability to induce GJ formation.…”
Section: Discussionmentioning
confidence: 99%
“…Only the assembly of Cx32 into GJs appeared to be significantly facilitated by 9-CRA and ATRA as neither the assembly nor degradation of adherens junction associated proteins, E-cadherin and α and β catenin, were significantly affected although the assembly of tight junction associated protein, occludin, appeared to be enhanced. The significance of these findings is further underscored by the fact that both androgens and retinoids have been documented to maintain the polarized and differentiated state of epithelial cells of normal prostate and prostatic tumors [19], [42][45], and all have been shown to have pleiotypic effects by acting as transcription factors [1], [3], [5], [46]. Our findings also showed that Cx32 expression potentiated the growth inhibitory effect of androgens and retinoids in LNCaP-32 cells, which indicates that their growth inhibitory and chemopreventive effects in prostate might be related to their ability to induce GJ formation.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant dams were euthanized by CO2 asphyxiation and UGS tissue collected from resulting fetuses. For tissue separations 14 and 17 dpc UGS mesenchyme was enzymatically and mechanically separated from UGS epithelium and homogenized as described previously (22). …”
Section: Methodsmentioning
confidence: 99%
“…The prostate gland is an out pouching of the posterior endoderm and RA is both necessary and sufficient for the formation of prostatic buds [140]. Fgf10 is also essential for budding of the prostate [141].…”
Section: Retinoic Acid and Posterior Endodermmentioning
confidence: 99%